WARMING UP THE SCHOOL CLIMATE - PERCEPTION OF THE SCHOOL ENVIRONMENT AND PEER AGGRESSION - Frankowiak, Joanna Katarzyna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article sought answers to questions about the significance of subjectively perceived conditions of the school environment for students experiencing cyber aggression. The theoretical framework of the study was comprised by the socio-ecological concept of school environment (Bronfenbrener, 1986) and the concept of resilience explaining the phenomenon of positive adaptation of children and young people (Garmezy 1985). The research was carried out as part of a wider project oriented at introducing changes in schools and using a diagnostic survey. Participation was attended by: schools’ representatives, a local institution dealing with social prevention, and a researcher in the person of the author of the article.